Fluoropolymer microstructure and dynamics: Influence of molecular orientation induced by uniaxial drawing. (17th May 2016) - Miranda, Daniel F.; Yin, Chaoqing; Zhang, Shihai; Runt, James
Abstract: Fluorinated semi-crystalline polymers are attractive for dielectric film applications due to their chemical inertness and high thermal stability. In the present investigation we explore the influence of orientation induced by uniaxial drawing on the crystalline microstructure and relaxation processes of poly(ethylene-tetrafluoroethylene) (ETFE), in order to ascertain how morphological control can benefit polymer dielectric design. When drawn below or near the Tg, the crystallinity of the drawn films is unchanged, and oriented amorphous structures and crystalline microfibrils form at high draw ratios. This orientation slows segmental relaxation, reflected by an increase in the dynamic Tg . When drawing above Tg, the films undergo strain-induced crystallization at high draw ratios. For these films, an increase in dynamic Tg is also observed, in addition to a second segmental relaxation process, appearing as a shoulder on the primary process. We propose that this represents a contribution from a rigid amorphous fraction, having slowed chain dynamics. Graphical abstract: Highlights: Orientation induced by uniaxial drawing alters dynamics of fluoropolymer film. Strain-induced crystallization induces formation of rigid amorphous fraction. The induced crystallization only occurs when drawing above the glass transition.